Studies on Etiologies and Hemato-Biochemical Alterations Associated with Anemia in Goats - Rao, Neha; Parmar, Jignesh J.; Sadhu, Dasharath B.; Shah, Aditya I.; Patel , Deepak M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present investigation was carried out to study the incidence and etiological factors, including Hemato-biochemical changes associated with Anemia in goats presented at Veterinary Clinical Complex of the College of Veterinary Science and Animal Husbandry Anand for 2 years. Total 559 goats were suspected of Anemia, and 80 (14.31 %) goats were found anaemic. Sex-wise incidence was higher in females (72.50%, 58/80) than males (27.50%, 22/80). Age-wise incidence was higher in ≥1-year age group (66.25%, 53/80) as compared to <1-year age group (33.75%, 27/80). The season-wise highest incidence was recorded in monsoon (50.00%, 40/80), followed by winter (27.50%, 22/80), and in summer (22.50%, 18/80). Hematological parameters indicated significantly (p <0.05) decreased TEC, Hb, PCV, MCV, MCH, and MCHC, and significantly increased TLC and neutrophils in anaemic goats compared to healthy goats. Serum biochemical estimations indicated a significant reduction in SGPT and total protein levels in anaemic goats compared to healthy goats. The etiological study revealed the highest incidence for mixed endoparasitic infestation (48.75%) followed by poor nutrition (25%) and other causes, like coccidia and scabies (8.75% each) and Trypanosoma and lice-tick mixed infestation (3.75% each).